Brolucizumab for Wet Aged-Related Macular Degeneration Patients : too Good to be True: Oral Presentation - Observational Study - Resident - Supanji; Purbonegoro, Tania; Prayogo, M. Eko; Agni, A. Nurini; W., Tri Wahyu; W., Firman S.; Sasongko, M.B (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesBrolucizumab is the newest anti-vascular endothelial growth factor (anti-VEGF). It showed superioranatomic outcomes and noninferiority best corrected visual acuity (BCVA) results for Wet Aged-Related Macular Degeneration (Wet-AMD) compared to other anti-VEGF. In Yogyakarta, it's beenonly used in a few patients and we want to report the effectiveness and safety of brolucizumab inWetAMD MethodsIn this retrospective study, all wetAMD patients who underwent Brolucizuab intravitreal injectionsbetween December 2021 and January 2023 at Dr YAP Eye Hospital were studied. Patient’sdemographic data, before and after intravitreal brolucizumab injections (central macular thickness,intraocular pressure, and BCVA) were assessed. ResultsThis study included 6 eyes of 6 patients (3 women) with a mean age of 69.5 years old. The meanfollow-up period was 27 ± 10.1 weeks after the first injection of brolucizumab. Three patients werenaïve wetAMD patients, three anti-VEGF experienced wetAMD patients. The mean BCVA at baseline(before brolucizumab injection) was 0.12 decimal (6/48) and 0.29 decimal (6/20) at the last followup.Five out of six patients' visual acuity were improved. In four out of six patient central macularthickness were reduced (mean difference 29,2 um). None of the patient's intraocular pressureincreased over 21 mmHg. None of the patients reported any signs of inflammation, vasculitis, ocularor systemic adverse effects. ConclusionThis limited data demonstrated that brolucizumab was relatively safe and effective in stabilizingBCVA for both WetAMD patients who had previous treatment with other anti-VEGF agents andnaive. Larger sample sizes studies & future multicenter collaborative are warranted